Reactive oxygen species‐responsive dual‐targeted nanosystem promoted immunogenic cell death against breast cancer - Asmita Banstola; Mahesh Pandit; Ramesh Duwa; Jae‐Hoon Chang; Jee‐Heon Jeong; Simmyung Yook (Wiley, 2023)
Abstract The development of an optimal treatment modality to improve the therapeutic outcome of breast cancer patients is still difficult. Poor antigen presentation to T cells is a major challenge in cancer immunotherapy. In this study, a synergistic immunotherapy strategy for breast cancer incorporating immune cell infiltration, immunogenic cell death (ICD), and dendritic cell (DC) maturation through a reactive oxygen species (ROS)‐responsive dual‐targeted smart nanosystem (anti‐PD‐L1‐TKNP) for the simultaneous release of DOX, R848, and MIP‐3α in the tumor microenvironment is reported. Following local injection, anti‐PD‐L1‐DOX‐R848‐MIP‐3α/thioketal nanoparticle (TKNP) converts tumor cells to a vaccine owing to the combinatorial effect of DOX‐induced ICD, R848‐mediated immunostimulatory properties, and MIP‐3α‐induced immune cell recruitment in the tumor microenvironment. Intratumoral injection of anti‐PD‐L1‐DOX‐R848‐MIP‐3α/TKNP caused significant regression of breast cancer. Mechanistic studies reveal that anti‐PD‐L1‐DOX‐R848‐MIP‐3α/TKNP specifically targets tumor tissue, resulting in maximum exposure of calreticulin (CRT) and HMGB1 in tumors, and significantly enhances intratumoral infiltration of CD4+ and CD8+ T cells in tumors. Therefore, a combined strategy using dual‐targeted ROS‐responsive TKNP highlights the significant application of nanoparticles in modulating the tumor microenvironment and could be a clinical treatment strategy for effective breast cancer management.